2020
DOI: 10.1038/s41598-020-61889-0
|View full text |Cite
|
Sign up to set email alerts
|

A 62K genic-SNP chip array for genetic studies and breeding applications in pigeonpea (Cajanus cajan L. Millsp.)

Abstract: Pigeonpea is the second most important pulse legume crop for food and nutritional security of South Asia that requires accelerated breeding using high throughput genomic tools. Single nucleotide polymorphisms (SNPs) are highly suitable markers for this purpose because of their bi-allelic nature, reproducibility and high abundance in the genome. Here we report on development and use of a pigeonpea 62 K SNP chip array 'CcSNPnks' for Affymetrix GeneTitan ® platform. The array was designed after filtering 645,662 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Considering the correlation between seed yield per plant and other characters, it was found that seed yield was positively correlated with number of pods per plant, number of seeds per pod and number of primary branches. Similar report was given by Bhadru (2010).The high yielding lines selected and studied for their molecular diversity using 62K SNP chip has confirmed the variations and correlations among the selected contrasting breeding lines (Singh et al, 2020). Hence, these characters namely seeds per pod and hundred seed weight have to be given importance during the selection programme to improve the yield potential of the crop.…”
Section: Correlation and Path Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…Considering the correlation between seed yield per plant and other characters, it was found that seed yield was positively correlated with number of pods per plant, number of seeds per pod and number of primary branches. Similar report was given by Bhadru (2010).The high yielding lines selected and studied for their molecular diversity using 62K SNP chip has confirmed the variations and correlations among the selected contrasting breeding lines (Singh et al, 2020). Hence, these characters namely seeds per pod and hundred seed weight have to be given importance during the selection programme to improve the yield potential of the crop.…”
Section: Correlation and Path Analysissupporting
confidence: 77%
“…Characterization and evaluation of available germplasm for different agro-morphological and biochemical traits is necessary to identify the effect of different genes on the phenotypes. We have already developed and evaluated high yielding lines in pigeon pea (Arumugam et al, 2018), identified diverse markers and validated the developed high yielding lines (Singh et al, 2020), genes and genes network were also being cracked (Chaudhary et al, 2017;Yasin et al, 2018;Yasin et al, 2019). In continuation to that, the present study was carried out with an objective to characterize two hundred selected pre-breeding accessions for the qualitative traits to estimate the genetic variability, heritability, coefficient of variation and character association analysis.…”
Section: Introductionmentioning
confidence: 98%
“…Legume genomes are rich in SNPs. Saturated map of SNPs were reported in legumes like vigna (55) and In pigeonpea (56). Of which highest haplotype desnsity of 0.7380 was reported for serine threonine kinase coding disease resistance gene (56) which was identified as an important miR target in the present ivestigation.…”
Section: Discussionmentioning
confidence: 93%
“…"C": cluster (colour figure online) (Singh et al 2016;Roorkiwal et al 2013;Saxena et al 2012;Kassa et al 2012). Similarly, in the case of pigeonpea, a number of datasets have been produced using NGS (Varshney et al 2012) and Cajanus SNP array (Saxena et al 2018;Singh et al 2020). These datasets have been used in several studies, for instance GBS for trait mapping (Saxena et al 2017a(Saxena et al , b, c, 2020, WGS for trait mapping, gene discovery, diversity, evolutionary analysis (Varshney et al 2017;Singh et al 2016), SNP array data for diversity analysis, trait mapping (Yadav et al 2019), etc.…”
Section: Discussionmentioning
confidence: 99%